Implementasi Pembelajaran Daring Bagi Siswa dan Guru MIS PSM Kepuhrejo - Mustajib (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Learning management is very important in its position in order to improve the effectiveness of the teaching and learning process, especially during the emergency spread of the Corona Virus Disease-19 (COVID-19) as we are currently experiencing. Various efforts were made to improve the quality of education while still considering the health protocol in accordance with Ministerial Decree 4. Various obstacles, difficulties, and limitations are faced in the teaching and learning process, ranging from factors of students, students' families, as well as facilities and infrastructure that are less representative, but the Ministry of Education and Culture (Kemendikbud) continues to instruct all educators at all levels of education in order to create a fun learning from home for both students and college students. Therefore, the teacher's role is very much needed in managing or managing to learn starting from planning, organizing, implementing, and evaluating in order to increase the effectiveness of the teaching and learning process during the current COVID-19 pandemic, both the implementation of online and off-network learning. offline). This study aims to identify the implementation of teacher online learning management, the differences between face-to-face learning and online learning, and several things related to online learning due to the impact of covid-19. This research was conducted at MIS PSM KEPUHREJO KEDIRI. This study uses a qualitative approach with a descriptive method. Data were collected using interview techniques and documentation to the parties concerned. The results of the study show that the impact of covid-19 on the implementation of online learning can be carried out quite well despite some obstacles that occur. This can be done with the support of all parties